"Post‐election stress disorder?" Examining the increased stress of sexual harassment survivors after the 2016 election. (14th March 2022) - Fattore, Christina; Zhao, Xiaohui; Kelly, Kimberly M.; Murray, Pamela J.; Weiss, Karen; Patel, Jayeshkumar; Innes, Kim; Sambamoorthi, Usha; Misra, Ranjita
Abstract: Objectives: In this paper, we explore if Donald Trump's electoral success in 2016 led to heightened levels of stress for sexual harassment survivors. Methods: Logistic regression models predicting voter stress using original survey data collected in the weeks following the 2016 election were utilized. Results: We find that women survivors of sexual harassment experienced elevated stres when compared to women who were never harassed. Conclusion: Female survivors of sexual harassment may be concerned that their well‐being was under attack due to the triumph of hostile sexism.